Dukungan Sosial Keluarga dan Motivasi Belajar pada Mahasiswa Rantau di Jakarta - Rose, Stefanny; Monika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Family social support is a situation that provides benefits to individuals, obtained from a reliable family. Through this support, individuals feel confident that there are family members who care, love and appreciate them. Learning motivation can be interpreted as mental effort in the learning process, using strategies that support the teaching and learning interaction process, asking and practicing questions in the learning context, and considering the level of understanding and ability to relate new material to previous material. The aim of this research is to determine the relationship between family social support and the learning motivation of overseas students in Jakarta. Is there a relationship between family social support and the learning motivation of overseas students in Jakarta? The Student Social Support Scale family social support measuring tool was compiled by Malecki and Elliot (1999) and adapted by Elyana (2016) based on aspects of House theory (Smeet, 1994). The Motivated Strategic for Learning Questionnaire (MSLQ) learning motivation measuring tool was developed by Gracia & Pintrich (1996) and adapted by Elyana (2016) based on the theoretical aspects of Pintrich et al (2008). Based on data analysis using Pearson correlation, it was found that there was a relationship between family social support and learning motivation.